MYOFASCIAL SYMPTOMATOLOGY IN PATIENTS WITH JOINT AND MUSCLE, COMPRESSION AND DISLOCATION DYSFUNCTION OF TEMPOROMANDIBULAR JOINT - Rybalov, O.V.; Yatsenko, P.I.; Yatsenko, O.I.; Ivanytska, E.S. (World of Medicine and Biology, 2016)
The paper analyzes the results of a comprehensive examination of 89 patients with joint and muscle compression and dislocation dysfunction of temporomandibular joint (TMJ). The authors found that myofascial pain symptom in dysfunction of the joint has a distinct clinical course, which consists in causing muscular spasms and reducing the range of motions of the mandible, densifying in strained muscles (trigger points), presence of pronounced pain zones in the temporal and occipital areas, as well as the ear area. It was established that the cause of myofascial pain is associated not with morphological changes in the TMJ, but with functional disorders of the masticatory muscles, which can be combined with morphological ones. There is a probability of limited mobility of one of the joints or its temporary blocking which leads to severe reflex muscle changes.